Optimizing Systematic Land Registration (PTSL) to Enhance Legal Certainty of Land Ownership Rights: Collaboration with Religious Value in Indonesia - Fatahussalam Zaenuddin; Hemalia Zahra; Inka Febby Rahmayanti (Religion and Policy Journal)
Research Problem: Land disputes between the public and various stakeholders frequently arise in Indonesia, often due to limited public trust in the Complete Systematic Land Registration Program (PTSL). This distrust results in low participation in PTSL, affecting land security and legal ownership.